Development Strategy Implemented by the Koto Tinggi Village Government in Sarugo Tourism Village Using 4A Analysis (Attraction, Accessibility, Amenities, Ancillary) - Iqbal, Muhammad; Ernawati, Ernawati (Amalee: Indonesian Journal of Community Research and Engagement, 2025)
Tourism has experienced a paradigm shift from consumptive to participatory, where tourist villages are one form of tourism that emphasizes cultural interaction and community empowerment. This study aims to explore the development strategy of the Saribu Gonjong (Sarugo) Tourism Village in Nagari Koto Tinggi. The research method uses the Asset-Based Community Development (ABCD) approach and 4A analysis (attractions, accessibility, amenities, support). The stages include local asset mapping, participatory discussions, action planning, strategic role sharing, and field training. Data were collected through observation, interviews, documentation, and literature studies of key informants such as Pokdarwis, Bundo Kanduang, youth, and village officials. The study results showed that mentoring succeeded in identifying cultural and social assets, strengthening community capacity, and increasing collaboration between parties. Cultural attractions need to be packaged more thematically, while accessibility and amenities are still challenges. The village government plays an active role as a facilitator and regulator of tourism village development. This study concludes that through 4A analysis it is effective in encouraging the development of tourism villages based on local potential in a sustainable manner. Still, long-term success requires infrastructure improvements, further training, and ongoing cross-sector coordination.